The Recent Traditionalist Turn in Indonesian Islam After Conservatives: How its Engagement towards Urban Muslims - Jati, Wasisto Raharjo; Yilmaz, Ihsan (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The recent Indonesian Islamic wave in Indonesia appears to be inclined towards a traditionalist turn. This turn specifically denotes the ascendancy of traditional Islamic teachings as the forefront in Indonesia. The resurgence of traditionalism has consequently led to a decline in the influence of conservatives, that has dominated public preferences from the 2000s to early 2014. While these new waves are likely to persist due to strong government support for religious moderation programs. They provoke both favorable and unfavorable perspectives among urban Muslims. In light of this contentious stance, this paper seeks to explore why urban Muslims display a reluctance towards the traditionalist shift. To address this inquiry, the research employs critical discourse analysis based on literature reviews. The primary finding of this discussion is that as the traditionalist movement extends its influence into urban environments, urban Muslims communities tend to align themselves with conservative ideologies. This poses a challenge for traditionalists aiming to alter religious preferences in urban areas.